MRI assessment of percutaneous ablation of liver tumors: Value of subtraction images. Issue 2 (28th September 2012) - Tatli, Servet; Acar, Murat; Tuncali, Kemal; Sadow, Cheryl A.; Morrison, Paul R.; Silverman, Stuart G.
Abstract Purpose: To evaluate the value of subtraction images when using MRI to assess liver tumors treated with percutaneous ablation. Materials and Methods: Following percutaneous ablation of 35 liver tumors, two abdominal radiologists, blinded to outcomes, independently reviewed follow‐up MRI examinations for tumoral enhancement suggestive of residual/recurrent tumor and rated their confidence level. After one year, the readers reviewed the same examinations with added subtraction images. Accuracy of the detection of residual/recurrent tumor and contrast‐to‐noise ratios (CNR; for tumoral enhancement‐to‐liver, tumoral enhancement‐to‐ablation zone, and ablation zone‐to‐liver) were calculated with and without subtraction images and compared using Wilcoxon signed rank test. Interobserver variability was computed using Kappa (κ) statistics. Results: Residual/recurrent tumor was present in 8 (23.5%) of 34 tumors. Accuracy of detecting residual/recurrent tumor with subtraction images and interobserver agreement (κ = 0.72, good) were better than accuracy of detecting residual/recurrent tumor and interobserver agreement (κ = 0.57, moderate) of enhanced MR images without subtraction. Mean CNR of subtraction images was significantly higher than that of enhanced MR images for tumoral enhancement‐to‐liver (0.2 ± 5 versus 11.6 ± 14.4, P = 0.03), tumoral enhancement‐to‐ablation zone (10.1 ± 12.5 versus 34.4 ± 29.4, P = 0.02), and ablation zone‐to‐liver (11.8 ± 13.3 versus 102.5 ± 238.4, P = 0.03). Conclusion: When using MRI, subtraction images help both detect and exclude residual/recurrent tumor following percutaneous liver ablations. J. Magn. Reson. Imaging 2013;37:407–413. © 2012 Wiley Periodicals, Inc.